May Measurement Month 2022: results from the global blood pressure screening campaign (2024)
Introduction Elevated blood pressure (BP) is the major contributor to mortality and disease burden worldwide. May Measurement Month (MMM) is a global BP screening campaign, which aims to raise awareness of BP measurement and provide evidence to inform and influence related health policy. Methods This cross-sectional survey included individuals aged≥18 years recruited through opportunistic sampling at sites in 60 countries during MMM 2022. Each participant had three sitting BP measurements and a questionnaire was completed including demographics, comorbidities and lifestyle factors. Hypertension was defined as a systolic BP≥140 mm Hg and/or a diastolic BP≥90 mm Hg (average of the second and third readings) or taking antihypertensive medication. Multiple imputation was used to estimate BP readings where any participant’s BP readings were missing. Linear mixed effects models were used to identify associations between participant characteristics and systolic or diastolic BP. Results Of the 715 518 participants surveyed (excluding 50 200 self-measured home BP screenees recruited via the ZOE Health Study app), 257 421 (36.0%) were identified as hypertensive, of whom 57.6% were aware and 49.3% were on antihypertensive medication. Of all participants with hypertension, 26.1% were controlled to <140/90 mm Hg and 12.0% to <130/80 mm Hg. Of those taking antihypertensive medication, 52.7% were taking only one drug class, 52.9% were controlled to <140/90 mm Hg and 24.4% to 130/80 mm Hg. In total, 190 314 (26.6% of total surveyed, 73.9% of hypertensives) participants screened were found to have untreated or inadequately treated hypertension. Only 27.6% of treated hypertensive participants were taking a statin. Substantial coexistence of diabetes, overweight and hypertension was apparent among participants.